2017
DOI: 10.1080/10962247.2017.1315348
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal ambient particulate matter and population health outcomes among communities impacted by road dust in British Columbia, Canada

Abstract: There was a significant association between daily concentrations of the coarse fraction and nonaccidental mortality during the road dust season, even after adjustment for the fine fraction. The acute and chronic health effects associated with exposure to the coarse fraction remain unclear, which supports the maintenance of PM monitoring networks to allow for further research in communities affected by sources such as road dust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Road dust has been linked to a number of detrimental health outcomes: repeated exposure of mice to roadside PM has been shown to lead to pulmonary oxidative damage and systemic inflammation, 42 and springtime road dust emissions have been shown to be associated with an increase in daily mortality. 3,43 Our results provide missing, complementary information regarding the potential role of photochemistry in influencing the environmental lifetime of toxic pollutants associated with road dust, including PAHs and other contaminants that react via 1 O 2 -mediated pathways. 44 As vehicle exhaust emission regulations tighten in coming years, the relative contribution of road dust and other nonexhaust emissions (e.g., brake dust and tire tread particulate) to urban PM loadings will increase: 45,46 according to one prediction, non-exhaust PM will represent 80−90% of all PM emissions from road transport by the end of this decade.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Road dust has been linked to a number of detrimental health outcomes: repeated exposure of mice to roadside PM has been shown to lead to pulmonary oxidative damage and systemic inflammation, 42 and springtime road dust emissions have been shown to be associated with an increase in daily mortality. 3,43 Our results provide missing, complementary information regarding the potential role of photochemistry in influencing the environmental lifetime of toxic pollutants associated with road dust, including PAHs and other contaminants that react via 1 O 2 -mediated pathways. 44 As vehicle exhaust emission regulations tighten in coming years, the relative contribution of road dust and other nonexhaust emissions (e.g., brake dust and tire tread particulate) to urban PM loadings will increase: 45,46 according to one prediction, non-exhaust PM will represent 80−90% of all PM emissions from road transport by the end of this decade.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…In both Canada and the United States, dust from paved and unpaved roads is the largest anthropogenic source of primary fine particulate matter (PM 2.5 ). 1,2 As a result of accumulation of sand and other winter traction materials applied to roadways, the level of dust emission from paved roads often peaks in the spring; 3,4 however, road dust has also been shown to contribute to PM 10 and PM 2.5 loadings throughout the year in a wide variety of urban locations. 5−8 Unlike desert dust, which is primarily composed of crustal material, 9 road dust is a complex mixture that also includes particles from road surface, brake, and tire wear; traction materials; semivolatile components of vehicle exhaust; and vegetative detritus, including soil and humic materials.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the above exposure assessment methods, evidence for an association between exposure to wildfire smoke and all-age mortality is mixed. Four of five studies reported small increases in wildfire smoke associated mortality among all ages, however, all confidence intervals included the null [18][19][20][21]. The fifth study reported positive odds ratios (ORs) on lag days 0, 2, 3, and 4, but not on lag day 1 [22].…”
Section: Introductionmentioning
confidence: 95%
“…The U.S. Environmental Protection Agency (EPA) regulates both PM 10 and PM 2.5 , PM with a diameter of 10 or 2.5 µm or less, respectively. The deposition of suspended PM is of concern to aquatic and vegetative health ( 6 – 8 ), as is the interception of airborne PM by the human respiratory system ( 9 ). Although PM 10 is referred to as the “coarse particulate” fraction, it can settle into the trachea or bronchi, exacerbating conditions such as asthma, chronic obstructive pulmonary disease, and emphysema ( 5 , 10 ).…”
mentioning
confidence: 99%